Legal Analysis of Termination of Employment Case in Industrial Court Decision Number 24/Pdt.Sus-PHI/2015/PN.Kpg. - Alamsyah, Fiqih Dien; Sifana, Firdha; Simanjuntak, Max Doan; Tarina, Dwi Desi Yayi (DE'RECHTSSTAAT, 2025)
Termination of employment is an event that often occurs in an employment relationship between workers/laborers and employers. The case involving Albert Wadu as a permanent employee of Kupang Beach Hotel with his leadership and KPN Maju, is a case of violation of rights and obligations after unilateral termination carried out by Kupang Beach Hotel by not applying applicable legal regulations in Indonesia regarding this matter. The research method used is normative legal research method. The results of this study indicate that in dealing with factors that influence termination of employment, companies need to make firm decisions in accordance with applicable regulations, namely Law No. 11 of 2020 Article 154A. In addition, employees can also terminate employment if they feel uncomfortable or there are other influencing factors. In this case, the company needs to take firm action in terminating employment and fulfill the requirements based on applicable regulations, namely Law No. 11 of 2020 Article 154A. In Law Number 2 of 2004 there are procedures for resolving industrial relations disputes and including the settlement of disputes over termination of employment (PHK), this law states that there are 3 ways to resolve disputes over termination of employment, namely, Bipartite, Tripartite and Industrial Relations Court.